Main Results of the Questionnaire for Portuguese Entities Potential Users of Construction and Demolition Recycled Materials (C&DRM). (2016) - Freire, Ana Cristina; Martins, Isabel M.; Ferreira, Cláudia; Gonçalves, Jorge; Roque, António José; Pinto, Isabel
Abstract: Within the framework of the activities of the working group GT1 of the Portuguese Commission on Transportation Geotechnics – Promote the use of non-traditional materials in embankments and structural layers – a questionnaire addressed to potential national entities as construction and demolition recycled materials, C&DRM, producers/users was designed. The main objective was to collect information about the various types of C&DRM produced/used, its main characteristics and respective fields of application, in particular for civil engineering works and transport infrastructures. The answers to the survey provide insight into the national distribution of different types of C&DRM and respective applications both in terms of type and in terms of amount of material applied and in the near future could be used to elaborate a map of recycled aggregates in Portugal.